Laleonectes Manning & Chace 1990 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Laleonectes Manning & Chace, 1990 Type species. Neptunus vocans A. Milne-Edwards, 1878 [Type locality: Cape Verde Islands]. Remarks. Laleonectes currently consists of four species: L. kuriya Mendoza & Devi, 2017 (WIO); L. nipponensis (Sakai, 1938) (IWP); L. stridens Crosnier & Moosa, 2002 (SP); and L. vocans (AA). Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 54, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155